Pengembangan Aplikasi Doa Harian menggunakan Metode Hybrid untuk Web dan Mobile - Faisal Ayash Fikrian; Ahmad Rio Adriansyah (LPPM STT Terpadu Nurul Fikri, 2022)
Dua is a series of worship related to the perfection of a Muslim's faith. In Islam, there are many prayers so that Muslims can remember their daily prayers, and media is needed to facilitate it. The media that is easy to use, and almost everyone has it, is a smartphone. Currently, prayer applications on smartphones have been widely developed, but based on surveys and observations made by the author to prayer application users, there are perceived shortcomings, including annoying ads, unattractive interface, unclear writing, and slow performance. This study aims to build an application that is attractive and convenient to use. This application is built with several technologies, including React Native Framework and Laravel. The development method used in this study uses the Waterfall method and UML Diagrams as the design system. The result of this research is an Android-based prayer collection application with several features: prayer list, prayer search, favorite prayer, prayer reminder, prayer category, prayer sharing, and prayer manager admin. Based on the System Usability Scale test with an average score of more than 85 points, it can conclude that the prayer collection application that has been built in this study is attractive and comfortable to use by a Muslim.